Arvon yhteisluonnin mikromekanismit tekoälysovellusten ammatillisessa käytössä: käyttökokemuksia ostoreskontran kontekstissa - Vehmanen, Jutta (2024)
The master's thesis examines how accounts payable specialists perceive artificial intelligence (AI) in professional use. The study aims to deepen the understanding of AI in professional use and the value it creates for the organization's employees. The study explores user experiences through a service-centered lens using the micro-level mechanisms of value creation. The empirical part of the qualitative research is conducted using the critical incident technique and thematic analysis method. The analysis revealed three categories of use cases within which 48 critical experiences were identified. Of these experiences, 37 support value co-creation, and 11 involve value co-destruction. The results are reviewed within a framework that categorizes the data according to the micro-level mechanisms of value creation. The findings indicate that artificial intelligence usage experiences are associated with both hedonic and utilitarian values. The study finds that the participation of specialists in the use of AI applications enables a user-centric approach that promotes value co-creation. Positive experiences with AI, such as improved efficiency, highlight value co-creation, while errors in use or users' distrust of the application can lead to value co-destruction. Key factors supporting value co-creation include reliability, user-centricity, and a balance between various benefits. Theoretically, the study provides information on how micro-level mechanisms apply to the topic and how AI usage is perceived in professional contexts. The research identifies value-enhancing factors associated with AI usage as well as the challenges that arise. The results demonstrate that AI usage can encompass both hedonic and utilitarian characteristics.